Crouzon’s syndrome: a new surgical approach - Madhumati Singh, Dr.; Kishore Felix, Dr.; Anjan Kumar Shah, Dr. (International Journal of Dental Research, 2019)
Crouzon’s syndrome is a rare genetic disorder characterized by distinctive malformations of the skull and facial region, premature cranial suture closure is the most common skull abnormality, optic disc edema and proptosis are among the most common ocular findings. It is a genetic disorder of gene FGFR-2 (Fibroblast Growth Factor Receptor-2) in 95% of cases, and in 5% of cases, FGFR-3 (Fibroblast Growth Factor Receptor-3) mutation occurs.Once a suture becomes fused, growth perpendicular to that suture becomes restricted and the fused bones act as a single body structure. Compensatory growth occurs at the remaining open sutures to allow continued brain growth, resulting in abnormal bone growth and producing facial deformities.In the new born child, some potential problems that may need to be addressed include respiratory difficulties, feeding problems, neurologic complications such as hydrocephalus and the potential risk of developmental delay.We represent a literature review and a rare case of Crouzon’s Syndrome, who wanted facial correction to be done at the age of 24years. We planned two stage surgical procedure, for correction of facial deformity.